Jane Eyre's Conservative Canadian Cousin: The Nymph and the Lamp - Friesen, Peter (Studies in Canadian Literature, 1990)
When compared, the plots of Thomas Head Raddall's The Nymph and the Lamp and Charlotte Brontë's Jane Eyre appear to be quite similar, yet neither Raddall himself nor any Raddall scholars have ever included Brontë among Raddall's influences. This may be because, even though The Nymph and the Lamp borrows heavily from Jane Eyre's plot, it shares none of the latter novel's feminist spirit. Moreover, Raddall's novel is not only similar in plot to Jane Eyre, it may also be a calculated response to the earlier book, for the messages of the two novels are substantially opposite: where Brontë expounds a progressive feminist cause, Raddall's cause is conservatively (even regressively) patriarchal. Hence, Raddall's borrowing from Brontë's novel is, in a sense, ironic as it undermines and subverts the feminist message of Jane Eyre.